Legal scholarship for new law teachers - Ross Buckley (Legal Education Review)
This article considers four issues for new law teachers: why write, what to write, how to write and where to write (in the sense of where to get published). I was prompted to write it by memories of how mystifying the scholarly process had been for me. The article attempts to systematise some approaches to legal scholarship and to consider anecdotally those which work for me.